2017
DOI: 10.1093/cvr/cvx118
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes secreted by cardiomyocytes subjected to ischaemia promote cardiac angiogenesis

Abstract: This study establishes that exosomes secreted by cardiomyocytes under ischaemic conditions promote heart angiogenesis, which may pave the way towards the development of add-on therapies to enhance myocardial blood supply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
159
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(173 citation statements)
references
References 30 publications
3
159
0
Order By: Relevance
“…In each case, the mechanisms of EV secretion and uptake are highly regulated, and can be affected in response to various cellular stressors, including ischaemia . Mounting evidence has demonstrated that EVs are major conveyors of biological information, being able to deliver complex mixtures of cargo in a targeted manner, modulating the behaviour of receptor cells . In the heart, EVs secreted by adult mouse cardiomyocytes were shown to modulate gene expression in fibroblasts and activate endothelial cells .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In each case, the mechanisms of EV secretion and uptake are highly regulated, and can be affected in response to various cellular stressors, including ischaemia . Mounting evidence has demonstrated that EVs are major conveyors of biological information, being able to deliver complex mixtures of cargo in a targeted manner, modulating the behaviour of receptor cells . In the heart, EVs secreted by adult mouse cardiomyocytes were shown to modulate gene expression in fibroblasts and activate endothelial cells .…”
Section: Introductionmentioning
confidence: 99%
“…EV secretion of heat shock protein (Hsp)60, a known activator of toll‐like receptor (TLR)4, by cardiomyocytes was reported to be upregulated in response to hypoxia . Recently, we showed that cardiomyocytes subjected to ischaemia release EVs that promote the growth of new vessels in the heart . Nevertheless, cardiomyocyte‐macrophage crosstalk via EVs remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…H9C2 myoblasts subject to hypoxic conditions secrete exosomes enriched for miRs related to cell proliferation and differentiation including miR‐143 and miR‐222. In corollary experiments, the exosomes derived from the hypoxic cells induced endothelial proliferation, migration, and survival under stress …”
Section: Understanding the Paracrine Effects Exerted By Exosomes Secrmentioning
confidence: 98%
“…The effects of cardiomyocyte‐derived exosomes were either proangiogenic or antiangiogenic, dependent on the conditions of release, which affected their miR cargo. Cardiomyocyte‐secreted exosomes were also found to be involved in the transfer of functional angiotensin II type 1 receptors ( AT 1Rs) under conditions of stress and involved in HSP 90 (heat shock 90‐kDa protein)–dependent regulation of collagen synthesis in fibroblasts in models of hypertrophy . Serum and plasma exosomes arise from a variety of cell sources, and the diversity of their effects results from the disease status and conditions of release.…”
Section: Understanding the Paracrine Effects Exerted By Exosomes Secrmentioning
confidence: 99%
“…Although gastric cancer biomarkers and theranostics have made great advance [23,24,25,26]; some miRNAs have also been found to be associated with gastric cancer stages [27], how the exosomal proteins involved in the progression of cancer still lacks report. Li, et al reported that exosomal proteins were used for cancer diagnosis, were potential biomarkers [28], and could also be used for cardiac angiogenesis [29], tumor therapy [30] and (hepatitis B virus) HBV therapy [31]. Tumor cell-derived exosomes could be used for tumor therapy [32].…”
Section: Urinary Exosomes Proteomics Analysismentioning
confidence: 99%